Rethinking MYC inhibition: a multi-dimensional approach to overcome cancer’s master regulator - Yu, Jing; Liu, Dan; Yuan, Yujian; Sun, Chunxia; Su, Zihan (Frontiers in Cell and Developmental Biology, 2025)
MYC, a master regulator in oncogenesis, has long been deemed “undruggable” due to its intrinsically disordered structure. However, recent advances are overturning this view, with direct inhibitors like Omomyc (OMO-103) and PROTAC-based degraders such as WBC100 showing promising clinical progress. Complementary strategies—including BET and CDK9 inhibitors, RNA-based therapeutics, nanobodies, and engineered proteases—are expanding the therapeutic landscape. Despite challenges in specificity, toxicity, and delivery, these innovations underscore MYC’s emerging druggability. Moreover, combination therapies integrating MYC inhibitors with chemotherapy, radiotherapy, or immunotherapy demonstrate synergistic potential. This article advocates for a multi-dimensional, biomarker-guided approach to MYC targeting, emphasizing rational drug combinations and continued innovation to overcome resistance and improve outcomes in MYC-driven cancers.